Aplikasi Metode Tahlili dan Ijmali Dalam Fiqh Al-Hadis - A. Gazali, Muh. Rakasiwi; Asse, Ambo; Ngempo, Muhammad Ali (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the science of hadith there are three methods of Shariah that are often used, namely tahlili and ijmali. Both methods have their drawbacks and advantages so it is necessary to learn them in order to use them appropriately. In this library study, through a qualitative approach, the author discusses Tahlili and ijmali Methods. The results of the study show that the methods of tahlili and ijmali in hadith commentators are the methods that are commonly used by hadith commentators. Each method has its respective advantages and disadvantages as different intricacies arise in its application. Thus, it becomes something urgent to understand that whatever method the narrator applies to a hadith cannot be said to be an end product with absolute truth as it is still open to compare it with the same product yet using different methods.